Le développement professionnel en évaluation des apprentissages d’enseignants du supérieur - Isabelle Nizet; Josée-Anne Côté; Christelle Lison (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
The general objective of our study is to provide tools to identify traces of professional development among teacher-researchers in different disciplines who are training evaluation in the Evaluating in Authentic Situations course offered online as a credited university training. This course is part of a microprogram designed from the perspective of the Scholarship of Teaching and Learning (Bélisle et al., 2016). Artifacts from three complex tasks competed in this course are analyzed with reference to the different parameters of Clarke and Hollingsworth's (2002) dynamic professional development model and the identity and cultural dimensions of university teachers' evaluative skills (Nizet, 2015). We propose a critical review of this model in the light of the intelligibility of evaluative practices, since the performance of complex tasks in the course leads to awareness and identity and cultural shifts, signs of authentic professional development within the framework of institutional constraints and dominant evaluative cultures.